Design and Development of an Autonomous Solar-Powered Artificial Beehive Acoustic Deterrent System for Human–Elephant Conflict Mitigation - Ariffin, Muhammad Aliff Zuhairi; Mohamad, Khairul Anuar; Nordin, Mohamad Syahmi; Hairul Hafizi Hasnan; Ahmad Fateh Mohamad Nor; Rohaiza Hamdan; Nazirah Mohamad Abdullah; Nor Anija Jalaludin (Journal of Science and Technology, 2026)
This paper presents the development of a solar-powered artificial beehive system designed to mitigate human–elephant conflict, overcoming the limitations of conventional deterrent methods that lack sustainability and autonomous operation. The proposed system integrates solar energy, adaptive acoustic deterrence, and smart sensing into a unified off-grid solution for continuous field deployment. The system is powered using a 50-watt solar panel and a 12V 8Ah lead-acid battery, with an ESP32 microcontroller interfacing with passive infrared (PIR) and ultrasonic sensors to enable context-aware triggering of sound outputs. The ultrasonic sensor generates frequency responses based on object proximity, producing 200 Hz for long-range detection (above 200 cm), 250 Hz for mid-range detection (100–200 cm), and 500 Hz for close-range detection (below 100 cm). The PIR sensor immediately activates a 2000 Hz signal upon motion detection. The acoustic output is amplified using a TDA2030 module and delivered through a 15-watt horn speaker. Experimental evaluation under controlled and simulated conditions demonstrated stable system operation, with the system remaining inactive in the absence of sensor inputs and producing frequency-based acoustic outputs corresponding to detected conditions. Solar performance over five days showed consistent energy generation of more than 30 W under clear conditions, with battery voltage reached 13.17 V, indicating the capability for sustained autonomous operation. The results confirm the functional integration of sensing, control, and energy subsystems for adaptive acoustic response in off-grid environments.